Exploring LGBTQ + health literacy in Australia: survey co-design and study protocol for a descriptive cross-sectional study - Karina Chalouhi; Julie Mooney-Somers; Melody Taba; Kirsten J McCaffery; Lucy Watson; Julie Ayre (Health Literacy and Communication Open, 2025)
Background Health literacy for LGBTQ+ people in Australia is under-researched and sparsely researched internationally. Existing health literacy surveys may not adequately capture the specific health literacy issues that LGBTQ+ people face, and existing research does not adequately explore the diversity and nuances of health literacy experiences within the community.Aims To address these research gaps, this project aimed to:Co-design a cross-sectional survey to explore health literacy and health information needs in the LGBTQ+ community. This includes both individual health literacy (the skills that allow individuals to access, understand, and use information for the benefit of their own health) and distributed health literacy (skills available to an individual through their social ecosystem).Co-develop an accompanying protocol to implement the survey.Methods We developed a prototype survey to assess personal and distributed health literacy patterns, strengths, and challenges, and health information needs and preferences. A Working Group comprising 12 LGBTQ+ interest holders guided refinement of the initial prototype via four online co-design workshops. For the protocol, the Working Group co-designed and co-decided strategies for recruitment, distribution, reciprocity, and knowledge dissemination. Co-design principles were used to ensure survey was grounded in community.Discussion This project outlines the co-design of a survey and protocol that aim to provide rich and meaningful insights into the health literacy of LGBTQ+ people in Australia. Such data will provide an evidence base that can inform policy direction and decisions about LGBTQ+ health literacy, and support services to meet health information needs of the community.